Zooarchaeological assemblages contextualize the historical ecology and harvest of fur-bearing mammals in Vermont - Mychajliw, Alexis M.; Hsi, Audrey Y.; An-Pham, Drew; Olson, Olivia L.; Carder, Nanny; Crock, John G.; Robinson, Francis “Jess” W. (Frontiers in Ecology and Evolution, 2023)
Shifting baselines can skew species harvest guidelines and lead to potentially inaccurate assessments of population status and range. The North American Fur Trade (~1600-1900 CE) profoundly impacted the continent’s socio-ecological systems, but its legacies are often not incorporated in management discussions. We apply a conservation paleobiology lens to address shifting baselines of nine species of fur-bearing mammals in Vermont, including seven mesocarnivores and two semi-aquatic rodents. Using a database maintained by the Vermont Division for Historic Preservation, we identified 25 existing radiocarbon dates of fur-bearer associated features from 16 archaeological localities spanning the Early-Late Holocene. We also generated 7 new radiocarbon dates on beaver and muskrat bones from the Ewing (VT-CH-005), Bohannon (VT-GI-026), and Chimney Point (VT-AD-329) localities. Our new radiocarbon dates cluster within the Late Holocene, immediately prior to and throughout the European contact period, and overlap with The Beaver Wars. We recover a ~8,000 year record beaver harvest, affirming the millennial scale importance of beavers, which are often foci of human-wildlife conflict. Comparison of zooarchaeological occurrences with digitized natural history specimens and community science observations reveals geographic range continuity for most species except for the American marten, which was historically extirpated, and confirms the native status of the red fox. While taphonomic constraints make our dataset a conservative assessment, our case studies demonstrate how wildlife managers can employ zooarchaeological data to better understand long-term properties of coupled socio-ecological systems and highlight the cultural importance of these species to Indigenous trade networks prior to the Fur Trade in Vermont.